Development of a novel bioceramic root canal sealer and its effect on the dislodgement resistance and dentinal tubule penetration - Lin, Galvin Sim Siang (2023)
The present study aimed to fabricate and characterise novel algin-incorporated bioactive glass 58S calcium-silicate root canal sealer (Bio-G) and evaluate its effect on the dislodgement resistance and dentinal tubule penetration to root dentinal walls in comparison to commercially available bioceramic-based sealers (BioRoot RCS and iRoot SP). Three groups of bioactive glass (BG) 58S powders were synthesised using sol-gel method and characterised using SEM, HRTEM and FTIR for optimisation: BG-1 (no ammonia), BG-2 (3 ml of ammonia), and BG-3 (5 ml of ammonia). Optimised BG-3 was used to fabricate the powder form of experimental Bio-G sealer with the addition of calcium silicate, zirconia dioxide, calcium carbonate and alginic acid powder. Meanwhile, the liquid form composed of 5% calcium chloride solution. The experimental 0-5% algin Bio-G sealers were then compared with BioRoot RCS and iRoot SP. Standardised disc specimens of mixed sealer materials (n=5 per group) were prepared and placed in an incubator to allow setting before characterising under SEM, HRTEM, EDS, FTIR and XRD. Next, one-hundred-and-seventy-six mandibular premolars were randomly assigned (n=16 per group): control, gutta-percha + 0-5% algin Bio-G, gutta-percha + BioRoot RCS, and gutta-percha + iRoot SP groups, with the exclusion of the control group in adhesive pattern and dentinal tubule penetration tests. They were instrumented, obturated and placed in an incubator for 72 hours to allow sealer set. For the dentinal tubule penetration test, sealers were mixed with 0.1% of rhodamine B dye. Subsequently, teeth were cut into a 1-mm-thick cross-section at 5-mm and 10-mm levels from the root apex, respectively. Push-out bond strength, adhesive pattern and dentinal tubule penetration tests were performed. Experimental Bio-G sealer revealed irregular micro-sized particles with a higher content of oxygen, silicon, and calcium, as well as trace of aluminium and chloride. Meanwhile, FTIR and XRD findings suggested that all sealers predominantly contained calcium silicate hydrate, calcium carbonate, and zirconium dioxide, while calcium aluminium silicate oxide was detected in 0-5% algin Bio-G. 5% algin Bio-G showed the highest mean push-out bond strength (p<0.05) with more favourable adhesion pattern, while iRoot SP showed the greatest sealer penetration (p<0.05). In addition, no significant association was noted between the dislodgement resistance and dentinal tubule penetration (p>0.05). In conclusion, the present novel Bio-G sealer demonstrated desirable particle size distribution and acceptable degree of purity. Algin-incorporated Bio-G showed favourable adhesive pattern with comparable dislodgement resistance and dentinal tubule penetration values to commercialised bioceramic-based sealers.